Optimization of Palm Oil Distribution Routes Using the Saving Matrix Approach and Genetic Algorithm on Capacitated Vehicle Routing Problem - Evi Yuliza; Yuli Andriani; Indrawati Indrawati; Sisca Octarina; Diah Putri Ramadani (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
The transportation of goods and services is a strategic issue in logistics systems, particularly in the palm oil industry. One of the key distribution optimization challenges is the Capacitated Vehicle Routing Problem (CVRP), which involves determining optimal distribution routes while considering vehicle capacity constraints. This study aims to identify the shortest distribution routes for transporting fresh oil palm fruit bunches from collection points to the palm oil mill, with the goal of minimizing total vehicle travel distance. A heuristic approach using the Saving Matrix method and a metaheuristic approach using a Genetic Algorithm were applied separately to two regions: Block P and Block Q, each consisting of 14 collection points with daily distribution schedules. The performance of both algorithms was analyzed and compared in the context of region-based distribution.The results show that the Genetic Algorithm yields more optimal solutions than the Saving Matrix, reducing the total travel distance by 33.92% in Block P and 32.81% in Block Q. In comparison, the Saving Matrix achieved reductions of 38.72% in Block P and 35.25% in Block Q. These findings indicate that the Genetic Algorithm performs better in solving CVRP for the distribution of fresh oil palm fruit bunches and can serve as a foundation for developing more efficient distribution systems using heuristic and metaheuristic approaches